Internet-Based Physician’s Workbench as User Interface for a Central Medical Case Repository - Kindler, H.; Baranov, A. E.; Fliedner, T. M.; Mall, H.; Engelke, A.; Densow, D. (Methods of Information in Medicine, 1999)
Two World Health Organization Radiation Medical Emergency Preparedness and Assistance Network centers have constructed a standardized central repository of acute radiation syndrome case histories. The case histories are stored on a database server. Radiation protection centers can remotely access the database by user-friendly client software over the Internet. Physicians can use the medical information system to retrieve similar case histories for decision support, to improve their medical knowledge by inspecting real case histories, and for research on the acute radiation syndrome. The system architecture is presented and it is shown in detail how the information system can be employed to deliver medical decision support. Dialogue-response times over narrow-bandwidth Internet connections are better than when using conventional World-Wide-Web technology. However, the latter does not require the installation of client software other than a browser. A JavaTM applet as client could combine the advantages of the two approaches.
Keywords: Medical Case Repository; Internet; Graphical User Interface; Decision Support System; Acute Radiation Syndrome; World-Wide-Web